A Practical Guide for Transparency in Psychological Science - Olivier Klein; Tom E. Hardwicke; Frederik Aust; Johannes Breuer; Henrik Danielsson; Alicia Hofelich Mohr; Hans Ijzerman; Gustav Nilsonne; Wolf Vanpaemel; Michael C. Frank (Collabra: Psychology, 2018)
The credibility of scientific claims depends upon the transparency of the research products upon which they are based (e.g., study protocols, data, materials, and analysis scripts). As psychology navigates a period of unprecedented introspection, user-friendly tools and services that support open science have flourished. However, the plethora of decisions and choices involved can be bewildering. Here we provide a practical guide to help researchers navigate the process of preparing and sharing the products of their research (e.g., choosing a repository, preparing their research products for sharing, structuring folders, etc.). Being an open scientist means adopting a few straightforward research management practices, which lead to less error prone, reproducible research workflows. Further, this adoption can be piecemeal – each incremental step towards complete transparency adds positive value. Transparent research practices not only improve the efficiency of individual researchers, they enhance the credibility of the knowledge generated by the scientific community.